Nurses' Perceptions Regarding Disclosure of Patient Safety Incidents in Selected Educational and Medical Centers of Iran University of Medical Sciences, 2020 - Alice Khachian; Mahnaz Seyedoshohadaee; Shima Haghani; Milad Ghanbari (Iran University of Medical Sciences, 2022)
Background & Aims: Patient safety is one of the most essential components of health care systems and is one of the most important pillars of quality in these organizations. Healthcare providers can improve a patient's safety status by interacting with patients and their families, controlling procedures, learning from mistakes, and communicating effectively with others on the health care team. Given that nurses spend more time caring for patients than other health care providers, they should be considered as the main group for planning to prevent and reduce the occurrence of medical errors. Increasing reporting and sharing of error information increases patient safety and prevents medical errors from recurring. Explicit disclosure of adverse events can maintain trust between health care providers and patients and reduce disputes and allegations of medical abuse. Therefore, considering the importance of patient safety, the researcher has decided to conduct a study with the aim of determining nurses' perception of the disclosure of patient safety. Materials & Methods: This descriptive cross-sectional study was conducted in the period of October to March 2020 in Tehran. The study population consisted of all nurses working in selected educational and medical centers of Iran University of Medical Sciences ( Rasoul Akram, Shahid Motahari, Shahid Hasheminejad, Shafa Yahyaian and Firoozgar Hospitals). The study was performed on 315 nurses. The sampling method in this stratified study was proportional .The tools used in this study consist of two parts: Demographic information form including questions about age, gender, marital status, education, employment status, work experience, work experience in other centers, ward, shift work and average overtime in Is the moon. Nurses' perceptions of the disclosure of patient safety incidents were measured using the Lee and Kim questionnaire. This questionnaire was translated and used for the first time in Iran. To determine the reliability of this questionnaire, the internal correlation of questions Cronbach's alpha and reproducibility were tested by test on 20 nurses at one week intervals, where Cronbach's alpha of the whole instrument was 0.885 and its intra-cluster correlation coefficient was 0.793. Analyzes were performed using SPSS software version 22 and using descriptive statistics (mean and standard deviation) and inferential statistics (independent t-test and analysis of variance). Finally, a significant level was considered less than 0.05 in the analyzes. Results: The results of the analysis showed that the general perception of nurses about the disclosure of patient safety Incidents with a mean of 55.66±13.20 (based on 0 to 100). The mean score (based on 0 to 100) was highest in the dimension of "nurses'perception of facilitators of open disclosure" with an average of 71.49 and in the dimension of "nurses' perception of the negative consequences of open disclosure" was the lowest with an average of 35.23. Nurses' perception of the disclosure of patient safety incidents had a statistically significant relationship only with the type of employment (P=0.04). A pairwise comparison showed that the average score of nurses with contract employment was significantly lower than formal (P=0.033) and contract (P=0.008). Also, the average score obtained in corporate nurses was significantly lower. It was less than conventional (P=0.029) and at other levels this difference was not significant. Conclusion: Based on the findings of the present study that nurses' overall perception of the disclosure of patient safety Incidents was positive, it is suggested that in order to improve patient safety Incidents disclosure, hospitals should create a positive culture in which explicit the disclosure of patient safety Incidents is first and foremost an opportunity Be considered to actively improve hospital safety. The people and the media must also create an atmosphere that reflects the trust and support of health care providers and institutions in exposing patient safety incidents. This allows healthcare providers to have positive perceptions of the disclosure of patient safety Incidents.